(untitled) (Al-Academy, 2016)
The Significance of this research comes as a result of the development occurring in various life fields including the field of technical and technological development in the domain of industrial products which are in direct touch with the receiver, and because the study of deletion and addition mechanism didn’t Find the Scientific space through researches and Studies. On this basis , the aim of this study is defining the forms of deletion and addition mechanism in designing the industrial product in a way that fits the functional presser . As to the limitations of this study, they involve examples of readymade Turkish House furniture, which is available in Iraqi local markets in Baghdad city 2013. The study included four chapters. The first chapter addressed the research significance and its need in addition to the research problem, aims and limitations, as well as terminology . As to the second chapter , it included previous studies and the theoretical frame work which in turn included three sections , the first came under the title " The Concept Of Deletion and addition in Design" , while the second section included the deletion and addition through design bases and elements , whereas the third sections included the action of functional presser in designing the industrial product . While the third chapter addressed the research procedures , Where the descriptive method was followed in analyzing the research sample till achieving the research aims, and relying on the research population which included three different examples of ready- made Turkish furniture which was selected deliberately to meet the research requirements and aims . Also, this chapter addressed the analysis of research sample according to the analysis axes defined by the researcher through the indicators revealed by the theoretical framework. Finally, the fourth chapter contained The results, conclusions , recommendations and suggestions